2016
DOI: 10.1186/s13148-016-0286-2
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free DNA promoter hypermethylation in plasma as a diagnostic marker for pancreatic adenocarcinoma

Abstract: BackgroundPancreatic cancer has a 5-year survival rate of only 5–7%. Difficulties in detecting pancreatic cancer at early stages results in the high mortality and substantiates the need for additional diagnostic tools. Surgery is the only curative treatment and unfortunately only possible in localized tumours. A diagnostic biomarker for pancreatic cancer will have a major impact on patient survival by facilitating early detection and the possibility for curative treatment. DNA promoter hypermethylation is a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 34 publications
3
75
1
1
Order By: Relevance
“…American Society of Anaesthesiologists (ASA) score and WHO performance status (PS) were registered at time of inclusion. Data from the same patients were used in a previous study …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…American Society of Anaesthesiologists (ASA) score and WHO performance status (PS) were registered at time of inclusion. Data from the same patients were used in a previous study …”
Section: Methodsmentioning
confidence: 99%
“…We previously performed a literature review to identify genes aberrantly methylated and detectable in cell‐free DNA from patients with pancreatic cancer . Additionally, we examined the hypermethylation of plasma‐derived cell‐free DNA as a diagnostic marker for pancreatic adenocarcinoma and found a panel of eight genes that could discriminate patients with pancreatic adenocarcinoma from patients with benign pancreatic disease or symptoms mimicking upper gastrointestinal cancer . The aim of this present study was to develop prognostic prediction models for pancreatic adenocarcinoma according to stage, based on a selected panel of hypermethylated promoter regions in plasma‐derived cell‐free DNA.…”
mentioning
confidence: 99%
“…There is potential for DNA methylation analysis to aid in early diagnosis and decrease cancer-specific mortality in this disease. A clinical cohort study published in 2016 demonstrated that interrogation of circulating blood DNA for methylation can identify patients with pancreatic adenocarcinoma (34). By examining methylation status at BMP3 , RASSF1A , BNC1 , MESTv2 , TFPI2 , APC , SFRP1 , and SFRP2, overt cancer was distinguished from healthy controls, as well as patients with chronic or acute pancreatitis with a sensitivity of 76% and specificity of 83% (34).…”
Section: Diagnostic Applications Of Dna Methylation Assaysmentioning
confidence: 99%
“…A clinical cohort study published in 2016 demonstrated that interrogation of circulating blood DNA for methylation can identify patients with pancreatic adenocarcinoma (34). By examining methylation status at BMP3 , RASSF1A , BNC1 , MESTv2 , TFPI2 , APC , SFRP1 , and SFRP2, overt cancer was distinguished from healthy controls, as well as patients with chronic or acute pancreatitis with a sensitivity of 76% and specificity of 83% (34). Diagnostic predictive accuracy was independent of tumor stage, suggesting that circulating DNA methylation may aid in early diagnosis of pancreatic cancer.…”
Section: Diagnostic Applications Of Dna Methylation Assaysmentioning
confidence: 99%
“…The aberrant methylation of some of the genes, such as BNC1 and ADAMTS1 , was shown to be detected in the serum of patients with PDA, which could be served as potential early diagnostic biomarkers for PDAs [23]. Cell-free DNA promoter hypermethylation in patient plasma was also shown to be significantly different between pancreatic cancer patients and control group [24]. Another study has examined DNA methylation differences in leukocyte DNA between PDA patients and controls [25].…”
Section: Dna Methylationmentioning
confidence: 99%